“Exploring the synergistic relationship between Pratylenchus penetrans and Verticillium dahliae in potato cropping systems: recent developments and research gaps” - Palmisano, Abigail; Parrado, Luisa; Quintanilla, Marisol (Frontiers in Horticulture, 2024)
The plant parasitic nematode species Pratylenchus penetrans has been known to form a synergistic relationship with the fungal plant pathogen Verticillium dahliae in potato cropping systems across North America. The results of this interaction can be devastating; with plants suffering from choloris, wilting, and premature death or complete yield loss in infected fields. Many studies have been conducted in order to understand how this symbiotic connection is occurring; whether that be from competition within the soil microbial community, through the development of amendment-induced suppressive soils, or from other interactions caused by nematode activity. While the mechanisms behind the hostile interaction between V. dahliae and P. penetrans are undetermined, the purpose of this review is to compile recent developments relating to this symbiotic relationship, the effects the soil microbial community has on said relationship, as well as identify potential gaps in research.